Induced pluripotent stem cells as natural biofactories for exosomes carrying miR-199b-5p in the treatment of spinal cord injury - Li, Jun; Jing, Yingli; Bai, Fan; Wu, Ying; Wang, Limiao; Yan, Yitong; Jia, Yunxiao; Yu, Yan; Jia, Benzhi; Ali, Fawad (Frontiers in Pharmacology, 2023)
Background: Induced pluripotent stem cells-derived exosomes (iPSCs-Exo) can effectively treat spinal cord injury (SCI) in mice. But the role of iPSCs-Exo in SCI mice and its molecular mechanisms still remain unclear. This research intended to study the effects and molecular mechanism of iPSCs-Exo in SCI mice models. Methods: The feature of iPSCs-Exo was determined by TEM, NTA, and western blot. The effects of iPSCs-Exo in SCI mice model were evaluated by BMS scores and H&E staining. The roles of iPSCs-Exo and miR-199b-5p in LPS-treated BMDM were verified by immunofluorescence, RT-qPCR and Cytokine assays. The target genes of miR-199b-5p were identified, and the function of miR-199b-5p and its target genes on LPS-treated BMDM was explored by recuse experiment. Results: iPSCs-Exo improved motor function in SCI mice model in vivo, shifted the polarization from M1 macrophage to M2 phenotype, and regulated related inflammatory factors expression to accelerate the SCI recovery in LPS-treated BMDM in vitro. Meanwhile, miR-199b-5p was a functional player of iPSCs-Exo, which could target Hgf. Moreover, miR-199b-5p overexpression polarized M1 macrophage into M2 phenotype and promoted neural regeneration in SCI. The rescue experiments confirmed that miR-199b-5p induced macrophage polarization and SCI recovery by regulating Hgf and PI3K signaling pathways. Conclusion: The miR-199b-5p-bearing iPSCs-Exo might become an effective method to treat the SCI.